2019
DOI: 10.1039/c8pp00472b
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence in the reaction of 1,2,4,5-tetraoxanes with ferrous ions in the presence of xanthene dyes: fundamentals and perspectives of analytical applications

Abstract: The reaction of biologically active bridged 1,2,4,5-tetraoxanes and diperoxide of trifluoroacetone with Fe2+ ions in the presence of xanthenes, methylene blue and methylene green is accompanied by bright chemiluminescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…It was found that 197a‐b had much lower AM activity (IC 50 > 10 −5 mol/L) toward D6 and W2 strains than 196 (WR 14899929) and tetraoxane 197c (Figure 49). 283–286 …”
Section: Some Antimalarial Endoperoxide Moieties Other Than 124‐triox...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that 197a‐b had much lower AM activity (IC 50 > 10 −5 mol/L) toward D6 and W2 strains than 196 (WR 14899929) and tetraoxane 197c (Figure 49). 283–286 …”
Section: Some Antimalarial Endoperoxide Moieties Other Than 124‐triox...mentioning
confidence: 99%
“…(Figure 49). [283][284][285][286] T A B L E 31 In vitro and in vivo activity of tetraoxanes against P. berghei. 288 It significantly reduced the parasitic liver burden in mice by up to 91% at 100 mg/ kg.…”
Section: 245-tetraoxanes Bearing Amino-alkyl Linkersmentioning
confidence: 99%